Upoštevanje etičnih načel kodeksa zdravstvene nege v Splošni bolnišnici Izola - Medoš, Tanja (Obzornik zdravstvene nege, 2004)
The article presents the results of a research study performed at the General Hospital Izola. The results illustrate actual consideration of the principles of ethics of nursing care. Individual ethical principles are related to patient's rights and to satisfaction with the work of nurses on the part of patients/clients.
Keywords: ankete; Bolnik, zadovoljstvo; bolnišnice; ethics; Ethics, Nursing; etika; Etika zdravstvene nege; medicinska etika; Medicinska sestra-bolnik, odnosi; Negovalne službe bolnišnične; Nurse-Patient Relations; Nursing Service, Hospital; Patient Satisfaction; Questionnaires; zdravstvena nega